Competence-based adaptation of learning environments in 3D Space - Nussbaumer, A.; Guetl, Christian; Albert, D.; Helic, D. (International Association of Online Engineering, 2009)
This paper presents a concept how a learning environment can be established in 3D space and how it can be adapted to the competence state of a learner. In contrast to existing Learning Management Systems learning paths are spatially represented in 3D space. In this approach the learner can immerse into a virtual learning landscape consisting of learning objects and is guided by highlighting a path through the landscape. Path creation is based on skills which are assigned to learning objects and which make up the learner model. Principles of the self-regulated learning approach is realised by visualising the learner model in 3D space and by giving the learner freedom for the own learning process. An implementation of this approach is realised in the Second Life virtual world which is connected with a Web service managing the adaptation strategy.